Evaluation of adhesion properties and antibacterial activities of the infant gut commensal Bifidobacterium bifidum PRL2010 - Serafini, Fausta; Strati, Francesco; Ruas-Madiedo, Patricia; Turroni, Francesca; Foroni, Elena; Duranti, Sabrina; Milano, Francesco; Perotti, Alessio; Viappiani, Alice; Guglielmetti, Simone; Buschini, Annamaria; Margolles, Abelardo; et al. (Anaerobe, 2013)
Bifidobacteria are extensively exploited by the food industry as health-promoting microorganisms. However, very little is known about the molecular mechanisms responsible for these beneficial activities, or the molecular players that sustain their ability to colonize and persist within the human gut. Here, we have investigated the enteric adaptation features of the gut commensal Bifidobacterium bifidum PRL2010, originally isolated from infant feces. This strain was able to survive under gastrointestinal challenges, while it was shown to adhere to human epithelial intestinal cell monolayers (Caco 2 and HT-29), thereby inhibiting adhesion of pathogenic bacteria such as Escherichia coli and Cronobacter sakazakii. •Bifidobacteria are exploited by the food industry as probiotic microorganisms.•There is a large paucity of data about their capabilities to colonize the human host.•Here we have characterized an infant gut commensal bifidobacterial strain.•This strain was shown to be able to survive under gastrointestinal challenges.•It is able to adhere to human epithelial intestinal cell.